Synthetic HLA-G proteins for therapeutic use in transplantation - LeMaoult, Joel (Federation of American Societies for Experimental Biology, 2013)
The human leukocyte antigen (HLA)-G is a tolerogenic molecule, whose expression by allografts is associated with better acceptance. An increasing interest in producing HLA-G as a clinical-grade molecule for therapy use is impaired by its complexity and limited stability. Our purpose was to engineer simpler and more stable HLA-G-derived molecules than the full-length HLA-G trimolecular complex that are also tolerogenic, functional as soluble molecules, and compatible with good manufacturing practice (GMP) production conditions. We present two synthetic molecules: (α(3)-L)(x2) and (α(1)-α(3))(x2) polypeptides. We show their capability to bind the HLA-G receptor LILRB2 and their functions in vitro and in vivo. The (α(1)-α(3))(x2) polypeptide proved to be a potent tolerogenic molecule in vivo: One treatment of skin allograft recipient mice with (α(1)-α(3))(x2) was sufficient to significantly prolong graft survival, and four weekly treatments induced complete tolerance. Furthermore, (α(1)-α(3))(x2) was active as a soluble molecule and capable of inhibiting the proliferation of tumor cell lines, as does the full length HLA-G trimolecular complex. Thus, the synthetic (α(1)-α(3))(x2) polypeptide is a stable and simpler alternative to the full-length HLA-G molecule. It can be produced under GMP conditions, it functions as a soluble molecule, and it is at least as tolerogenic as HLA-G in vivo.—LeMaoult, J., Daouya, M., Wu, J., Loustau, M., Horuzsko, A., Carosella, E. D. Synthetic HLA-G proteins for therapeutic use in transplantation.